Evaluation Results of Tracer Study as An Effort to Improve Teaching and Learning Activities at Widyatama University (Case Study: Graduate of the University of Widyatama graduating in 2017) - Eka Sumadhinata, Yelli (International Journal of Psychosocial Rehabilitation, 2020)
The Career Center of Widyatama University was formed based on Widyatama University Regulation No. 005 of the 2015 organizational structure. Career Center is a university supporting mengenai struktur organisasi carrier center universitas widyatama. Carrier Center is a university-supporting institution that carries out soft skill learning activities, job fairs, gatherings, and Tracer Study. Tracer study is conducted as an evaluation for institutions, especially in the effort to increase teaching and learning activities at Widyatama University. This research aims to conduct a search for university graduates and evaluate the results of tracer study graduates in 2017. The number of respondents who filled out the questionnaire was 384 people from 1302 total graduates in 2017. From the analysis of data processing, descriptive statistics are known as much as 60,94% of current graduates work. 63%. Respondents worked in the private sector, and the rest were scattered in the government sector, non-profit organizations, areas including state-owned enterprises as much as 23%, and entrepreneurs of 14%. Overall horizontal alignment of 79.5% means that the competence gained during the education in Widyatama according to the needs in the field of work, and from the results of the study obtained data that graduates who do work with the level of education is 78%. it means good